Revisiting antibody modeling assessment for CDR-H3 loop - Nishigami, Hiroshi (Protein Eng Des Sel, 2016)
The antigen-binding site of antibodies, also known as complementarity-determining region (CDR), has hypervariable sequence properties. In particular, the third CDR loop of the heavy chain, CDR-H3, has such variability in its sequence, length, and conformation that ordinary modeling techniques cannot build a high-quality structure. At Stage 2 of the Second Antibody Modeling Assessment (AMA-II) held in 2013, the model structures of the CDR-H3 loops were submitted by the seven modelers and were critically assessed. After our participation in AMA-II, we rebuilt one of the long CDR-H3 loops with 13 residues (A52 antibody) by a more precise method, using enhanced conformational sampling with the explicit water model, as compared to our previous method employed at AMA-II. The current stable models obtained from the free energy landscape at 300 K include structures similar to the X-ray crystal structures. Those models were not built in our previous work at AMA-II. The current free energy landscape suggested that the CDR-H3 loop structures in the crystal are not stable in solution, but they are stabilized by the crystal packing effect.